Peranan Pembimbing Kemasyarakatan Dalam Penanganan Kasus Perundungan yang Dilakukan oleh Anak - Suparman S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Abuses that are happening in Indonesia, even in educational institutions, which are places of self-development, are bullying. There is no protection for victims of bullying and even worse, sometimes educational institutions try to close the case so that the name of the school is not ruined. Prevention and handling of bullying is not only the role of educational institutions, but also the responsibility of parents, teachers, school staff and also the general public. All parties need to know that bullying is not an act of children that needs to be understood. The Ministry of Women's Empowerment and Child Protection (KemenPPPA) hopes that the case can be resolved with Restorative Justice according to what is mentioned in Act Number 11/2012 on the Child Criminal Justice System by resolving the case through diversion. One role that implements diversion is the Probation Officer. Probation Officers have the tasks and functions to help children who commit criminal offenses by seeking information to achieve diversion from the start of diversion on demand by investigators through a complete community information report compiled by the Probation Officer. The role of Probation Officer is divided into 3 stages, i.e. the stage before the court session (Pre-adjudication), the stage during the court session (adjudication) and the stage after the court (post-adjudication). The role of Probation Officer for Children Who Are Faced the Law is very important and necessary, this is because Probation Officers have their techniques and methods for handling Children Who Are Faced the Law which are based on regulations.